(untitled) (Fiep Bulletin - online, 2013)
The study had as objective to analyze the effects of the precocious initialization on gymnasts from the rhythmic gymnastics, as well to compare the beginning age of formation as gymnasts with their results and with the end of their sportive career. From the raised basis, we conclude we have several effects of the precocious initialization in those gymnasts and they change depending each one, considering the principle of the biologic individuality that involves the hereditarily, biotype and aspects socio-cultural where are included the gymnast’s locus and the modus Vivendi. As answer for our main statement, the basis leads us to certificate that the gymnasts who begun earlier show athletic longevity and results in championships that overcome the ones who begun later